1998
DOI: 10.1038/sj.onc.1202010
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cell adhesion by expression of the mutant neurofibromatosis type 2 (NF2) genes which lack exons in the ERM-homology domain

Abstract: Neurofibromatosis 2 (NF2) is an inherited disorder characterized by a predisposition to multiple intracranial tumors. The protein encoded by the NF2 gene has striking similarities to ezrin, radixin and moesin (ERM) proteins which link membrane proteins to the cytoskeleton. Therefore, it can be speculated that the disruption of cytoskeletal organization by alterations in the NF2 gene is involved in the development of tumors. It has been reported that the majority of NF2 mutations were nonsense or frameshift mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 12 publications
5
35
0
3
Order By: Relevance
“…The first 50 amino acids of merlin are required for the binding of merlin to CD44 and for inhibition of the CD44-HA interaction Studies have shown that merlin mutants lacking different portions of the NH 2 -terminal ERM-homology domain lose their ability to interact with the plasma membrane (Deguen et al, 1998;Koga et al, 1998), a finding that is consistent with the possibility that merlin engages CD44 using the segment(s) located in its NH 2 -terminal half. To define the domain of merlin that is required for its inhibitory effect on the CD44-HA interaction, we established five mutants each of which bore a 50-amino acid deletion within the first 250 residues of the NH 2 -terminal portion of merlin.…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 61%
See 3 more Smart Citations
“…The first 50 amino acids of merlin are required for the binding of merlin to CD44 and for inhibition of the CD44-HA interaction Studies have shown that merlin mutants lacking different portions of the NH 2 -terminal ERM-homology domain lose their ability to interact with the plasma membrane (Deguen et al, 1998;Koga et al, 1998), a finding that is consistent with the possibility that merlin engages CD44 using the segment(s) located in its NH 2 -terminal half. To define the domain of merlin that is required for its inhibitory effect on the CD44-HA interaction, we established five mutants each of which bore a 50-amino acid deletion within the first 250 residues of the NH 2 -terminal portion of merlin.…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 61%
“…These mutants are often associated with a more severe clinical outcome (Merel et al, 1995;Parry et al, 1996;Ruttledge et al, 1996;Deguen et al, 1998;Evans et al, 1998;Koga et al, 1998). It is widely held that tumor-suppressor mutants often act in a dominant-negative fashion to promote tumorigenesis (Nigro et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koga et al (1998) have recently shown that nuclear microinjection of a mutant NF2 cDNA lacking exon 2 sequences induces loss of cell adhesion in VA13 cells. These results indicate that exon-skipping mutations in the amino terminus of schwannomin cause a dominant effect on cell attachment.…”
Section: Discussionmentioning
confidence: 99%